KEBIJAKAN BAHASA TERHADAP PERAN BAHASA ASING DI INDONESIA: PERSPEKTIF EKOLOGI BAHASA - Koroh, Lanny Isabela Dwisyahri (Pendidikan Bahasa dan Sastra Indonesia Universitas Nusa Cendana, 2024)
Foreign languages ​​have a certain role in the context of the life of languages ​​in Indonesia. This function is realized in its use in certain domains, both natural and artificial based on language policy. In the Indonesian context, foreign languages, especially English, have an important role as a means of international communication. Ecologically, linguistic diversity in Indonesia requires a separation of functions and roles between local languages, Indonesian and foreign languages. In the context of language ecology, foreign languages ​​have the potential to dominate Indonesian and local languages. Regarding Indonesian, hegemony occurs because foreign languages ​​tend to have more economic value than Indonesian. Meanwhile, regarding local languages, foreign language hegemony is caused by low interdependence with local languages ​​in terms of structure and lexicon. In terms of language policy and language ecology, there are prescriptive matters that must be adhered to, but there are also descriptive matters related to the function and role of foreign languages ​​that need attention. Thus, foreign languages ​​will remain important in the context of global communication.